Critical Approaches to Welcome to Night Vale Podcasting between Weather and the Void (Springer International Publishing, 2018)
With well over one-hundred episodes, the podcast Welcome to Night Vale has spawned several international live tours, two novels set in the Night Vale universe, and an extensive volume of fan fiction and commentary. However, despite its immense popularity, Welcome to Night Vale has received almost no academic scrutiny. This edited collection of scholarly essays-the very first of its kind on a podcast-attempts to redress this lack of attention to Night Vale by bringing together an international group of scholars from different disciplines to consider the program's form, themes, politics, and fanbase. After a thorough introduction by the volume's editor, Jeffrey Andrew Weinstock, the eight contributors not only offer close analysis of Night Vale, but use the program as the impetus for broader explorations of new media, gender, the constitution of identity, the construction of place, and the human relationship to meaning and the non-human.